The role of NGOs in development cooperation: Some notes on empirical research findings - Rodger Wegner (Intereconomics, 1993)
There has been an impressive proliferation of non-governmental organizations in development cooperation in the last two decades. The main reason for this has been the belief—among both experts and the public at large—that NGOs have a number of advantages over the state sector when it comes to aid efficiency. The following article examines these apparent advantages and concludes that NGOs are often not nearly as effective in practice as the theory purports.
Keywords: 330; Non-Governmental Organizations